The Neuroprotective Effect of Byu d Mar 25 in LPS-Induced Alzheimer's Disease Mice Model. (27th February 2021) - Liu, Lan; Zhang, Yongcang; Tang, Liang; Zhong, Hua; Danzeng, Dunzhu; Liang, Cuiting; Liu, Shanling
Abstract : Inflammatory factors play an important role in the pathogenesis of Alzheimer's disease (AD). Byu d Mar 25 (BM25) has been suggested to have protective effects in the central nervous system. However, the effect of BM25 on AD has not been determined. This study aims to investigate the neuroprotective effect of BM25 in AD. A total of 40 AD model mice were randomly assigned to the following five groups ( n = 8 per group): the AD + NS group, the AD + donepezil group, and three AD + BM25 groups treated with either 58.39 mg/kg (AD + BM25-L), 116.77 mg/kg (AD + BM25-M), or 233.54 mg/kg BM25 (AD + BM25-H). The Morris water maze test was performed to assess alterations in spatial learning and memory deficits. Nissl staining was performed to detect Nissl bodies and neuronal damage. The expression of IL-1 β and TNF- α was evaluated by ELISA. The protein expression of P-P38, P38, P-I κ B α, caspase 1, COX2, and iNOS was determined by western blotting. The expression of A β, p-Tau, and CD11b was measured by immunohistochemistry. The mRNA expression levels of IL-1 β, TNF- α, COX2, and iNOS were measured by qRT-PCR. Spatial memory significantly improved in the AD + BM25-M and AD + BM25-H groups compared with the AD + NS group (p < 0.05 ). The expression of A β and p-Tau significantly decreased in the AD + BM25-M and AD + BM25-H groups (p < 0.05 ). The neuron density and hierarchy and number of pyramidal neurons significantly increased in the AD + BM25-M and AD + BM25-H groups (p < 0.05 ). In addition, the expression levels of CD11b, IL-1 β, TNF- α, COX2, iNOS, caspase 1, p-I κ B α, and p-P38 significantly decreased in the AD + BM25-M and AD + BM25-H groups (p < 0.05 ). In conclusion, our findings suggest that BM25 may exert anti-inflammatory and neuroprotective effects in AD model mice by suppressing the activity of microglia and inhibiting the phosphorylation of I κ B α and p38 MAPK.